The relationship between customer participation in the service innovation process and customer satisfaction - Altıok, Enis. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
As active co-creatorsof services rather than passive buyers, customers can act as a crucial source of innovation for service providers. Thus, the latter are willing to involve the former in their service innovation process (SIP). Past studies indicate that one of the ultimate consequences of customer participation in the SIP is customer satisfaction. Against this background, this study investigates the impact of customer participation in the SIP on their satisfaction with service providers and their services in the context of business-to-business relationships. Customer participation in the SIP is analyzed along five dimensions, namely, customer motivation, stages of participation, intensity of participation, channels of participation and relationship quality. Theories of motivation and aresource-based view of the firm are used to shed light on impact of customer participation in the SIP on customer satisfaction. Data was collected from the Turkish Courier, Express and Parcel (CEP) industry through a survey. In order to examine the effects of these dimensions on customer satisfaction, nonparametric statistical techniques were usedon a sample of 91 corporate customers of a leading CEP company. The findings of the study demonstrate that the quality of relationship between the customer and service provider and the use of a larger number of channels of participation have a positive influence on customer satisfaction. On the other hand, although customer motivation, stages of participation and intensity of participation have statistically significant positive correlations with customer satisfaction, they do not emerge as its significant predictors.
Keywords: Service industries -- Technological innovations.